2021
DOI: 10.1136/bmj.m4948
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cereal grains intake with cardiovascular disease and mortality across 21 countries in Prospective Urban and Rural Epidemiology study: prospective cohort study

Abstract: Objective To evaluate the association between intakes of refined grains, whole grains, and white rice with cardiovascular disease, total mortality, blood lipids, and blood pressure in the Prospective Urban and Rural Epidemiology (PURE) study. Design Prospective cohort study. Setting PURE study in 21 countries. Participants 148 858 participants with median follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 51 publications
4
41
1
Order By: Relevance
“…The term junk food is inherently colloquial (Hadjikakou and Baker, 2019). Palatable but unwholesome foods rife in fat, salt, and sugar (HFSS) and scarce in nutrients like proteins, vitamins, minerals, and fibers are junk foods (Stedman, 2012). Junk food has been interpreted and defined from a different perspective depending on its incidence in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term junk food is inherently colloquial (Hadjikakou and Baker, 2019). Palatable but unwholesome foods rife in fat, salt, and sugar (HFSS) and scarce in nutrients like proteins, vitamins, minerals, and fibers are junk foods (Stedman, 2012). Junk food has been interpreted and defined from a different perspective depending on its incidence in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Such foods also contain different preservatives that may be toxic if taken in a large amount. Also, maximum consumption of white flour/ refined flour used in producing various food products and packaged foods leads to serious health issues (Swaminathan et al, 2021). In Nepal, the percentage of households consuming biscuits/cookies is 95.6 % according to the Nepal National Micronutrients Status Survey (NNMSS) 2016 (MOHP et al, 2018), which indicates the consumption of prepacked foods is rapidly increasing in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…We already know that adherence to a diet pattern such as the traditional MD [ 6 ] was associated with a reduction in overall mortality, coronary heart disease, and cardiovascular disease. An overall high-quality diet that emphasizes a high consumption of polyunsaturated and monounsaturated fatty acids, raw vegetables, dairy, legumes, low-fat lean meats fat, fresh fish, bread (especially whole-grain bread), and wine in moderation, has been inversely associated with overall mortality, especially in the elderly [ 167 , 168 ]. In addition, a healthy diet of high quality can increase the number of years without disease and without disabilities [ 169 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning protein intake, an established dietary bias is that older people need to obtain more protein with their diet, even though they are not malnourished. The main objective of this advice is to first prevent sarcopenia, then to maintain a good state of health, which allows for the prevention of malnutrition, improving wound healing and faster recovery from acute illness [ 167 ]. Instead, these recommendations are in contrast with the results of basic research on animal models and with the results of observational studies on population cohorts, which on the contrary have shown that a low-protein, high-carbohydrate diet (LPHC) can delay aging and extend lifespan [ 123 , 133 , 142 , 159 , 172 ].…”
Section: Discussionmentioning
confidence: 99%
“…This misapplication of “bigger is better” to nutrition is not theoretical, but on prominent display in the peer-reviewed literature. 24,25 As with RCTs, large samples, particularly when spanning multiple countries, tend to garner special attention and reverence. 26 But when they violate the requirement that a given study population be subject to the same general effects of an exposure, they, too, are apt to propagate fallacies.…”
Section: The Bigger They Are…mentioning
confidence: 99%